Can AI Improve Outcomes in Critical Care Settings? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2018)
Artificial intelligence (AI) is poised to revolutionize critical care medicine, offering the potential to enhance patient care, optimize resource allocation,...
Keywords: AI in Clinical Decision Support; Improve; Outcomes; Critical; Artificial Intelligence; Healthcare; Patient Care